Social Participation in Adults with Aphasia - Bernath, Tamsyn (My University, 2006)
Social participation is one of the most debilitating effects of aphasia. Yet, to date no clear definitions or models of social participation have been developed that can be applied within aphasiology. In addition, generic stroke scales are still the outcome measures of choice within research. There is a need for patient-centred measures that accurately document and assess the experiences and perceptions of those with aphasia. Therefore, the current research aimed to investigate the social participation of adults with aphasia by extending patient-centred measures and encompassing the views of the families, particularly the spouses, of those with aphasia. Four crosssectional parallel single case studies were conducted that involved a protocol combining the quantitative measure of the ASHA FACS with the qualitative tools of semi-structured interviews and observations. In addition, social network analyses were completed for each participant. Overall, open coding of the individual participants’ results produced common themes among the people with aphasia and common themes among their spouses. Each participant reported significantly altered social participation, which permeated throughout the family unit and was felt considerably by the spouses of those with aphasia. The results are discussed in relation to current social models and approaches to intervention, while professional role expansion and the needs of the South African context are also considered. Furthermore, the concept of resilience and its implications for future research are discussed.
Faculty of Humanities; School of Human and Community development; MA Research Report
Keywords: Aphasia; debilitating effects; aphasiology; ASHA FACS